The effect of ZnO nanoparticle coating on the frictional resistance between orthodontic wires and ceramic brackets - Ahmad; Mojgan; Masumeh; Baharak (Tabriz University of Medical Sciences, 2016)
Background. Any decrease in friction between orthodontic wire and bracket can accelerate tooth movement in the sliding technique and result in better control of anchorage. This study was carried out to evaluate frictional forces by coating orthodontic wires and porcelain brackets with zinc oxide nanoparticles (ZnO). Methods. In this in vitro study, we evaluated a combination of 120 samples of 0.019×0.025 stainless steel (SS) orthodontic wires and 22 mil system edgewise porcelain brackets with and without spherical zinc oxide nanoparticles. Spherical ZnO nanoparticles were deposited on wires and brackets by immersing them in ethanol solution and SEM (scanning electron microscope) evaluation confirmed the presence of the ZnO coating. The frictional forces were calculated between the wires and brackets in four groups: group ZZ (coated wire and bracket), group OO (uncoated wire and bracket), group ZO (coated wire and uncoated bracket) and group OZ (uncoated wire and coated bracket). Kolmogorov-Smirnov, Mann-Whitney and Kruskal-Wallis tests were used for data analysis. Results. The frictional force in ZZ (3.07±0.4 N) was the highest (P <0.05), and OZ (2.18±0.5 N) had the lowest amount of friction (P <0.05) among the groups. There was no significant difference in frictional forces between the ZO and OO groups (2.65±0.2 and 2.70±0.2 N, respectively). Conclusion. Coating of porcelain bracket surfaces with ZnO nanoparticles can decrease friction in the sliding technique, and wire coating combined with bracket coating is not recommended due to its effect on friction.